Analisis Pengaruh Kualitas Produk, Citra Merek, dan Penggunaan Korean Brand Ambassador terhadap Minat Beli Konsumen Produk Skincare - Sekar Ayu Kartikaning Bonde; Yunita Primasanti; Erna Indriastiningsih (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The entry of K-Beauty trend in Indonesia has influenced the interest of skincare consumers in Indonesia. Indonesia. The local skincare market continues to grow every year leading to increased competition in the local cosmetic business in Indonesia. This study aims to examine how the influence of product quality, brand image product quality, brand image and Korean Brand Ambassador on consumer buying interest in local skincare products. local skincare products. The sampling method was carried out with the technique Non-Probability Sampling technique where data is obtained through distributing questionnaires to 250 respondents with the determination of the number of respondents using the formula. to 250 respondents by determining the number of respondents using the Lemeshow formula. Then the data analysis was carried out using multiple linear regression analysis multiple linear regression analysis with data processing carried out using IBM software SPSS version 23 which then the data is analyzed and the results of the research are obtained in the form of: (1) Product Quality has a positive and significant effect on consumer interest in local skincare products, (2) Product Image consumer buying interest in local skincare products, (2) Brand Image has a positive and significant effect on consumer buying interest in local skincare products. significant effect on consumer buying interest in local skincare products, (3) Korean Brand Ambassador has a positive and significant effect on consumer purchase intention local skincare products, and (4) Product Quality, Brand Image, and Korean Brand Ambassador together have a positive and significant effect on consumer buying interest in local skincare products. Ambassadors together have a positive and significant effect on consumer buying interest in local skincare products